2021
DOI: 10.1002/jmri.28010
|View full text |Cite
|
Sign up to set email alerts
|

Application of Simultaneous 18F‐FDG PET With Monoexponential, Biexponential, and Stretched Exponential Model‐Based Diffusion‐Weighted MR Imaging in Assessing the Proliferation Status of Lung Adenocarcinoma

Abstract: Background Ki‐67 proliferation index (PI) is important for providing information on tumor behavior, treatment response, and prognosis. Integrated positron emission tomography/magnetic resonance (PET/MR) may have the potential to assess Ki‐67 PI in patients with lung adenocarcinoma. Purpose To explore the value of simultaneous 18F‐fluorodeoxyglucose (18F‐FDG) PET/MR‐derived parameters in assessing the proliferation status of lung adenocarcinoma and to determine the best combination of parameters. Study Type Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…Our study showed that Ki67 was positively correlated with μ and negatively correlated with ADC and D, which is consistent with the results of Huang et al. ( 39 ). The explanation may be as follows: as the proliferation activity of tumor cells increased the cell density increased, the free diffusion of water molecules decreased, and the μ value increased, while the ADC and D values decreased correspondingly.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that Ki67 was positively correlated with μ and negatively correlated with ADC and D, which is consistent with the results of Huang et al. ( 39 ). The explanation may be as follows: as the proliferation activity of tumor cells increased the cell density increased, the free diffusion of water molecules decreased, and the μ value increased, while the ADC and D values decreased correspondingly.…”
Section: Discussionsupporting
confidence: 93%
“…However, to the best of our knowledge, no authoritative investigations have reported the value of DDC in assessing the Ki-67 proliferation status in EC. In the present study, there was no significant difference in DDC between the highproliferation and low-proliferation EC groups, which is not consistent with the findings of the previous studies related to glioma (33) and lung cancer (31). We speculate that this may be related to the fact that there are more factors within high-proliferation EC that promote the diffusion movement of water molecules, such as a richer blood supply and more necrotic components, and that DDC is unable to separate these factors as effectively as D does (9,34,35).…”
Section: Evaluation Of Ivim For Eccontrasting
confidence: 99%
“…D is one of the quantitative parameters of biexponential model IVIM and theoretically reflects the diffusion movement of water molecules in the tissue more realistically because the effect of microcirculatory perfusion is excluded (9,10). Previous studies have shown that lesions with higher Ki-67 expression have higher cell densities, tend to have more significant water molecule restriction, and have smaller D values (30,31). In the present study, D was significantly lower in the high-proliferation group than in the low-proliferation group and was one of the independent predictors for the discrimination between the two groups, which is consistent with the findings of previous studies and suggests that D value has a positive significance in the prediction of Ki-67 status in EC.…”
Section: Evaluation Of Ivim For Ecmentioning
confidence: 99%
“…In this study, both ADC and MD values were weakly negatively correlated with the Ki-67 index, and these results are similar to those of Peng et al (28), further indicating that ADC and MD can be used for the assessment of Ki-67. One explanation is that the higher the Ki-67 index is, the stronger the tumor invasive ability, the higher the cell density, and the higher the nucleocytoplasmic ratio (29), which leads to the restricted diffusion of intracellular and extracellular water molecules, which in turn leads to a decrease in ADC and MD values (30). This study further explored the value of ADC and MD in evaluating NSCLC stage, and the results showed that there was no significant correlation between ADC, MD and NSCLC stage, which was similar to the results of Paul's study (31).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the SUVmax value was weakly positively correlated with the Ki-67 index, indicating that SUVmax can initially predict proliferation status. The reason may be that a high Ki-67 index often means that tumor cells have strong proliferation ability and vigorous metabolism (29), so their glucose uptake increases and SUVmax value increases. This study further analyzed the correlation between MTV, TLG and Ki-67, but the results showed that there was no significant correlation between them and Ki-67 expression.…”
Section: Discussionmentioning
confidence: 99%